Evaluating the impact of school-based influenza vaccination programme on absenteeism and outbreaks at schools in Hong Kong: a retrospective cohort study protocol - Chuhan Miao; Qingyang Lu; Yuqian Wu; Jianxun He (BMC, 2024)
Abstract Introduction Seasonal influenza causes annual school breaks and student absenteeism in Hong Kong schools and kindergartens. This proposal aims to conduct a retrospective cohort study to evaluate the impact of a school-based influenza vaccination (SIV) programme on absenteeism and outbreaks at schools in Hong Kong. Methods The study will compare schools that implemented the SIV programme with schools that did not. The data will be sourced from school records, encompassing absenteeism records, outbreak reports, and vaccination rates. We will recruit 1000 students from 381 schools and kindergartens in 18 districts of Hong Kong starting June 2024. The primary outcome measures will include absenteeism rates due to influenza and school influenza outbreaks. Secondary outcomes will consist of vaccination coverage rates and the impact of the SIV programme on hospitalisations due to influenza-like illness. A t-test will be conducted to compare the outcomes between schools with and without the SIV programme. Ethics and dissemination The school completed signing the participants' informed consent form before reporting the data to us. Our study has been approved by the Hospital Authority Hong Kong West Cluster IRB Committee (IRB No: UW 17-111) and was a subtopic of the research "The estimated age-group specific influenza vaccine coverage rates in Hong Kong and the impact of the school outreach vaccination program". Trial registration This study will be retrospectively registered.